Gender dan Kebudayaan : Analisis Antropologi - Sambayang, Zahwa Fibrilia; Nurkhamiden, Aisyah Aqneshia; Minabari, Farah (Jurnal JINNSA (Jurnal Interdipliner Sosiologi Agama), 2024)
This study aims to explore the relationship between gender and culture through an anthropological approach, with a primary focus on literature analysis. This study utilizes a variety of literature sources, including key theories such as gender performativity, intersectionality, and gender representation in cultural rituals. With a literature approach, this study critically reviews academic works from various disciplines, including anthropology, gender studies, and sociology, to develop a comprehensive theoretical framework. The results of the study show that gender construction cannot be separated from the cultural context that surrounds it. Cultural rituals play an important role in both reinforcing and challenging existing gender norms. In addition, the analysis shows that there is diversity in the concept of gender across cultures, such as the existence of non-binary gender categories in certain indigenous communities. This study also reveals that globalization and social dynamics contribute to the transformation of gender norms in modern society.